Purple Auroral Rays and Global Pc1 Pulsations Observed at the CIR‐Associated Solar Wind Density Enhancement on 21 March 2017. Issue 20 (18th October 2018) - Shiokawa, K.; Ozaki, M.; Kadokura, A.; Endo, Y.; Sakanoi, T.; Kurita, S.; Miyoshi, Y.; Oyama, S.‐I.; Connors, M.; Schofield, I.; Ruohoniemi, J. M.; Nośe, M.; et al.
Abstract: This paper reports two unique auroral features: postmidnight purple auroral rays and global Pc1 geomagnetic pulsations, observed before the onset of the corotating interaction region (CIR) storm of 21 March 2017, at the beginning of the first campaign of the new Particles and Waves in the Inner magnetosphere using Ground‐based network observation (PWING) longitudinal ground network with the Arase satellite. The purple auroral rays were observed from 0315 to 0430 UT ( 03–04 magnetic local time) in the northeastern sky at Husafell, Iceland (magnetic latitude: 64.9°N). We newly propose that the entry of high‐density CIR plasma into the magnetotail created purple auroral rays in the sunlit ionosphere. Pc1 geomagnetic pulsations at frequencies of 0–0.5 Hz were observed after 00 UT over a wide local time range, of 13 hr, from midnight to afternoon sectors at subauroral latitudes associated with CIR arrival. These results indicate preconditioning of the magnetosphere due to crossing of a CIR. Plain Language Summary: We report auroral ray structures, which show a unique purple color, and global geomagnetic pulsations observed on 17 March 2017. The purple auroral rays were observed in the northeastern sky at Husafell, Iceland. The geomagnetic pulsations at frequencies of below 0.5 Hz were observed over a wide longitudinal range extending from midnight through morning to afternoon sectors at subauroral latitudes. These phenomena took place associated with the arrival of the so‐called corotating interaction region (CIR)" in the interplanetary space, which is characterized by high‐density high‐speed solar wind plasma. The CIR is one of the phenomena frequently occurring during the minimum phase of the 11‐year solar cycle. We suggest that the CIR can cause these unique purple auroras and global geomagnetic pulsations. The present observations also suggest a possible mechanism for dropout of radiation belt electrons due to electromagnetic ion cyclotron waves (=geomagnetic pulsations) associated with the CIR arrival. Key Points: Unique postmidnight purple auroral rays and global Pc1/EMIC waves were observed during a CIR‐driven solar wind density enhancement Pc1/EMIC waves were found over a wide longitudinal range extending from midnight through morning to the afternoon due to CIR arrival Entry of high‐density solar wind plasma into the magnetotail may have created tall purple auroral rays in the sunlit ionosphere